A spirituality of compassion as a common good in times of God’s absence? - Domsel, Maike Maria (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2024)
Since Christian values have lost their monopoly position in postmodern European societies, a diversity of world views has developed. This has led to an understanding of a common set of values becoming a challenge, including in the school sector. Religious education, in particular, has the important task of supporting pupils in dealing with the diversity mentioned above responsibly. In the face of crises, the challenge of maintaining a constructive and respectful social dialogue becomes particularly relevant. Thus, the question emerges concerning whether and how a common spirituality can be built regarding leadership in secondary education. This study investigates whether the guiding principles of compassion and comparative theology suit the challenges of the aforementioned spiritual heterogeneity. Its focus lies in the common goal of overcoming global crises, such as the COVID-19 pandemic and warlike violence, to achieve a shared responsibility for the planet. This is exemplified through the practical implementation of the Erasmus+ project “yEUr Water – Row on it! Care for it!”, which aims to raise awareness of water preservation within schools across several European countries. It is found that the guiding principle of compassion, along with comparative theology, proves crucial in navigating spiritual heterogeneity, recognizing diverse beliefs, fostering unity, and acknowledging differences within worldviews.